Canada and missions for peace : lessons from Nicaragua, Cambodia and Somalia - Miller, Robert, 1941-; Wirick, Gregory ([NetLibrary], 1998)
Canada and Missions for Peace explores Canada's involvement in recent international efforts to resolve violent conflicts in Nicaragua, Cambodia, and Somalia. It examines the complex interface between foreign policy, international security, and international development. In doing so, this book joins the ever-growing body of scholarship on the new peacebuilding agenda, offering a unique vantage point: It focuses on the motivations, dynamics, and impacts of Canadian foreign policy -- It situates the Canadian effort within three very different and complex conflicts: Nicaragua, Cambodia, and Somalia -- and It provides sobering insight and useful recommendations to guide future policy and programing in peacebuilding. Perhaps it is too early to tell if a concern for international security can be combined with a concern for human security and well-being to form a new peacebuilding "architecture." The lessons and insight contained in Canada and Missions for Peace, however, will bring this vision into clearer focus